2015
DOI: 10.1007/s12311-015-0698-0
|View full text |Cite
|
Sign up to set email alerts
|

LTD, RP, and Motor Learning

Abstract: Long-term depression (LTD) at excitatory synapses between parallel fibers and a Purkinje cell has been regarded as a critical cellular mechanism for motor learning. However, it was demonstrated that normal motor learning occurs under LTD suppression, suggesting that cerebellar plasticity mechanisms other than LTD also contribute to motor learning. One candidate for such plasticity is rebound potentiation (RP), which is long-term potentiation at inhibitory synapses between a stellate cell and a Purkinje cell. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Different contributions of LTD and RP to VOR and OKR adaptation have also been reported. In delphilin knockout mice, LTD is more easily induced than in wild-type mice and OKR adaptation is facilitated 10 , whereas VOR adaptation is not 11 . In RP-deficient transgenic mice, VOR adaptation is suppressed but OKR adaptation is not 8 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Different contributions of LTD and RP to VOR and OKR adaptation have also been reported. In delphilin knockout mice, LTD is more easily induced than in wild-type mice and OKR adaptation is facilitated 10 , whereas VOR adaptation is not 11 . In RP-deficient transgenic mice, VOR adaptation is suppressed but OKR adaptation is not 8 .…”
Section: Discussionmentioning
confidence: 95%
“…Although the roles and regulatory neuronal pathways are similar between VOR and OKR, differential regulations of VOR and OKR by cerebellar synaptic plasticity mechanisms have been reported 8, 10, 11 . In addition, Faulstich et al .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the re-acquisition of locomotion can be considered to be a low level form of motor learning, in which repeated activity leads to sustained changes in the central nervous system such that spinal circuits below the site of a lesion can produce locomotor activity in the absence of descending motor commands. In this light, it is therefore instructive to consider that circuits that mediate short-term adaptation are those that lead to long-term learning through various mechanisms (Hirano et al, 2016). We have previously shown that dI3 INs mediate short-term adaptation in regulating paw grasp in response to changing sensory stimulation (Bui et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in other domains, supervised learning is thought to result from long-term depression of parallel fiber-purkinje cell synapses (and long-term potentiation of parallel fiber and interneuron synapses) in the cerebellum (De Zeeuw et al, 1998;Ito, 2002;Jorntell, 2016;Hirano, Yamazaki & Nakamura, 2016), implicating γ-aminobutyric acid (GABA-ergic) dependent plasticity (e. g., Lee et al, 2015). Phosphorylation mechanisms that are dependent on sustained protein kinase activation may regulate AMPA receptor internalization and long-term depression in the cerebellum, as suggested recent neurobiological computational (Gallimore et al, 2016).…”
Section: Mechanism?mentioning
confidence: 99%